How vulnerable is fiscal policy in Central and Eastern European countries? - Andreea Stoian (Romanian Journal of Fiscal Policy (RJFP), 2012)
The aim of this paper is to investigate the vulnerability of fiscal policy in the case of 10 Central and Eastern European countries. We use a newly introduce indicator named Cumulative Excess of the Primary Balance (CEPB) which shows the deviations of current fiscal policy from a fiscal rule implying the stabilization of the public debt. Using annual data extracted for 1996-2010 period, we find no evidence of fiscal vulnerability in the case of Bulgaria and Estonia. For rest of the countries the results indicate more or less fiscal vulnerability depending how large CEPB is.
Keywords: E62; H62; H63; 330; Fiscal policy; Primary balance; Public debt; Fiscal sustainability